Les fautes de traduction : une analyse pédagogique - Gile, Daniel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractTranslation errors are analyzed on the basis of an operational translation Model. They can be classified either according to their location in the Model's components (knowledge base, hypothesis formulation, plausibility, fidelity and acceptability tests), or according to functional criteria. Isolation and explicitation strategies help locate their sources. Two practical strategies are suggested for remedial action against errors arising from weak motivation in the students: one aims at heightening their awareness of the importance of particular aspects of translation, and the other puts pressure on specific components of translation through marking tactics.